Islamic Boarding School Leadership and Work Environment on Teacher Performance - Siregar, Zulfikar Ali Buto; Akmal, Syarifah; Mohzana, Mohzana; Rahman, Khalid; Putra, Freddrick Tiagita (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2023)
This research aims to identify gaps in existing research to improve the quality of teacher performance in the future. To achieve this objective, the study poses two research questions. Firstly, the research aims to analyze the influence of leadership in Islamic boarding schools (madrasah) and the working environment on teacher performance, both separately and collectively. Secondly, the research aims to identify and analyze variables that have a dominant influence in this context. These questions will be directed to respondents who have knowledge or understanding relevant to the research theme, which includes the leadership of madrasah principals, the working environment, and teacher performance. Based on the foregoing description, the preliminary results of this research indicate that leadership in the madrasah and the working environment significantly influence teacher performance. In other words, the more effective the leadership in the madrasah and the supportive working environment, the higher the level of teacher performance that can be achieved. Additionally, the research suggests that the role of madrasah leadership has a more dominant influence on teacher performance compared to other factors considered in this study. This research is a quantitative study with a survey approach. The data used are primary data obtained directly from 86 respondents through questionnaires. The findings of this study confirm that both madrasah leadership and the working environment have a simultaneous and partial influence, with madrasah leadership being the more dominant factor affecting teacher performance.